Konflik sosial dalam novel “Ganjil-Genap” karya Almira Bastari berdasarkan perspektif Lewis A.Cooser - Imam, M. Nasiful (Maliki Interdisciplinary Journal, 2023)
Social conflict is a unity of reality in social life. Lewis A. Cooser argues that social conflict is an integral part of social life and has certain roles and functions in society. This study aims to (1) describe the forms and causes of social conflict in the novel Odd-Even by Almira Bastari based on the perspective of Lewis A. Cooser; (2) describe the resolution of social conflict in the novel Odd-Even by Almira Bastari based on the perspective of Lewis A. Cooser. Pinip research uses qualitative-descriptive and library research methods. Researchers collect data by means of library research and intensive critical reading and note-taking techniques to identify the results of social conflict from Lewis A Cooser’s perspective. The overall data validation technique for this research is through the stages of increasing persistence in finding data sources, triangulation, and discussions between colleagues. The results of the research show that the social conflict in the novel consists of: (1) two forms of social conflict, namely: a. interpersonal conflict with two forms of social conflict, namely arguing and tension; b. personal conflict with a group with one form of social conflict: Selfishness (2) two conflict resolutions, namely stalemate and defeat by one of the parties.